Adverse event monitoring of the human papillomavirus vaccines in Scotland. Issue 4 (7th April 2016) - Cameron, R. L.; Ahmed, S.; Pollock, K. G. J.
Abstract : Background: Human papillomavirus (HPV) vaccines are currently utilised globally in national immunisation programmes. While evidence from clinical trials and epidemiological studies suggest that the HPV vaccines are both effective and safe, concerns about the safety of the vaccine and scientifically unproven associations with severe adverse events following immunisation have led to dramatic decreases in vaccine uptake in Japan and acceptance issues in other countries. Aim: In Scotland, we utilised hospital admissions data to assess the impact of the HPV immunisation programme on the incidence of 60 diagnoses between 2004 and 2014 in both girls and boys; with boys acting as a comparator group. Methods: Tabular and graphical outputs of the number of admissions, the incidence and the incidence ratio of 59 diagnoses were created to assess trends before and after the introduction of the HPV vaccine. Data linkage was utilised to investigate further the increase in Bell palsy diagnoses. Results: Fifty‐four diagnoses showed no change in incidence following the introduction of the national immunisation programme, and while small increases in incidence were observed for Bell palsy, coeliac disease, ovarian dysfunction, juvenile onset of type 1 diabetes, demyelinating disease and juvenile rheumatoid arthritis, none was statistically significant. Conclusions: Consistent with previous evidence, we present disaggregate data that reiterate the safety of both HPV vaccines.